Addressing weight stigma in physiotherapy: Development of a theory-driven approach to (re)thinking weight-related interactions. (3rd August 2017) - Setchell, J.; Gard, M.; Jones, L.; Watson, B. M.
ABSTRACT: In this article, we propose a theory-driven approach to developing interventions for reducing weight stigma in physiotherapy and discuss the design and exploratory trial of such an intervention. Weight stigma has been identified in physiotherapists in empirical investigations. However, there has been little consideration of how this stigma might be addressed. We highlight Goffman's work on stigma that provides social and embodied understandings of stigma. Goffman's approach, however, is notably apolitical, ahistorical and lacks mechanisms for understanding power. We suggest that post-structuralist perspectives can provide insight into these areas. Drawing on these theories, we critically examine the literature on weight stigma reduction, finding that trials have largely been unsuccessful. We argue that this may be due to overly passive and simplistic intervention designs. As context-specific understandings are desirable, we examine the nature of physiotherapy to determine what might be relevant to (re)thinking weight in this profession. We then discuss the development of a multifactorial, active weight stigma intervention we trialed with eight physiotherapists. Supported by theory, the outcomes of the exploratory study suggest that physiotherapy-specific factors such as fostering professional reflexivity and improving understandings of stigma need to be incorporated into an active intervention that considers the complex determinants of weight stigma.